Identification separation of cations in solid samples by using the reagent sodium carbonate (MACS) - Bazán Gutiérrez, D. (2003)
In this work we evaluate the tecnical alkaline, using the Reactive Carbonate-Soda adkacent so that we could make lhe separation and identlfication of Metals in solids specimens as minerals, silicates, etc. Deterrnination the most frequents elements in the Nature.